Pelatihan Pembuatan Mineral Tawas Berbahan Dasar Limbah Kaleng Bekas Bagi Masyarakat Sukmajaya, Depok - Riskaviana Kurniawati; Wiwik Dahani; Irfan Marwanza; Fadliah Fadliah; Arinda Ristawati; Muhammad Napis Fikri (Abdimas Universal, 2024)
All human activities inevitably produce waste. The amount of waste increases as the city grows. Sukmajaya District, Depok City is one of the districts that has the potential for very high waste accumulation. This area is a place for immigrants who work in Jakarta. This has a negative impact, namely the increase in the number of Final Disposal Sites (TPA) from year to year. The recycling process is a solution that can save energy and reduce landfill waste. The use of can waste as raw material in making alum or potassium aluminate sulfate K[Al(SO4)2.12H2O] is very relevant. The basic material used in making alum cans has the advantage of being more economical and can help reduce packaging can waste which has the potential to pollute the environment. The team held training in making alum minerals from used can waste in Sukmajaya District, Depok City. This activity aims to educate the public in utilizing used can waste into alum mineral products. People can use it to purify water in an environmentally friendly and economical way. The results of the training activities showed an increase in participants' awareness and skills in managing canned waste into value-added products. The number of training participants increased from 40% before training to 90% after training. Apart from that, participants' skills in making alum from used can waste also increased from 25% before the training to 85% after the training. It is hoped that this training can make a positive contribution in efforts to manage waste sustainably and protect the environment.